Collective building of a concept in nursing humanized care (2015)
The aim of this study was build a concept of humanized nursing care a collectively way in two university hospitals in Bogota DC. Method: It is a participatory dialectic qualitative research with an historical hermeneutic approach. Eight focus groups and one semi-structured interview were made for a total of 57 nurses. The construction was based on pre-concept took from theoretical framework, which was submitted for discussion among participants. The data analysis was done through content analysis methodology. Results: The final concept included six categories: integrity of the subject, dignity and human condition, ethical principles, scientific reflection, and assertive effective communication. It brings key elements for expression of the act of caring which may suggest that the humanized attribute is implicit in nursing care. Conclusion: This operational and limited conception no evidences a transcendent reflection about meaning of human being and humanization. The findings of this research were the basis for one diagnosis of humanized nursing care in institutions under consideration and for the search of alternatives to strengthen the humanization as a label in nursing services. © 2015, Universidad de Concepcion. All rights reserved.